Doha Merchandise Trade Reform : What is at Stake for Developing Countries? - Anderson, Kym; Martin, Will; van der Mensbrugghe, Dominique (Oxford University Press on behalf of the World Bank, 2013)
This article: a) summarizes the costs of current merchandise trade distortions to developing and other economies; b) examines some scenarios that might emerge as part of an eventual Doha agreement consistent with the 2005 Hong Kong Ministerial declaration, particularly with respect to agriculture; and c) draws implications for the strategies developing countries might adopt in the World Trade Organization's (WTO's) Doha round of multilateral trade negotiations. This article estimates what the world economy might look like in 2015 without and with a successful conclusion to the Doha round, how far Doha could take the world toward an outcome with no distortions in merchandise trade, and what contribution various elements of a Doha package could make.